2022
DOI: 10.1155/2022/2471681
|View full text |Cite
|
Sign up to set email alerts
|

Intermedia Agenda Setting amid the Pandemic: A Computational Analysis of China’s Online News

Abstract: Based on Intermedia Agenda Setting (IAS), the current study examines how official media and semi-privatized commercial media on the Weibo platform covered the COVID-19 pandemic in China. Both supervised machine learning and time series analysis were employed to analyze 350,059 Weibo posts released by 3,883 news sources between December 2019 and April 2020. Our results indicated that, in this nonwestern state-regulated China media environment, official and semi-privatized commercial media had a significant reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This is likely because Anshun bus accident is a public safety event, the coverage of which within the range of news, and official media have editorial rights, can find angles to obtain first-hand information, while commercial media can only reprint and integrate official media news, hence their dependence on official media is stronger. At the same time, official media not only have to conform to the Chinese Communist Party's views but also face market competition, which makes them have economic logic of increasing their user base and advertising revenue [29], especially local official media, which receive less state financial support. They need to create differentiated news to attract traffic and sustain themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because Anshun bus accident is a public safety event, the coverage of which within the range of news, and official media have editorial rights, can find angles to obtain first-hand information, while commercial media can only reprint and integrate official media news, hence their dependence on official media is stronger. At the same time, official media not only have to conform to the Chinese Communist Party's views but also face market competition, which makes them have economic logic of increasing their user base and advertising revenue [29], especially local official media, which receive less state financial support. They need to create differentiated news to attract traffic and sustain themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Buturoiu et al (2023) argue that after the pandemic crisis’s onset, traditional media’s power seems to have been transferred to online and digital media outlets. Wang and Shi (2022) highlighted the interaction between various social media news sources based on news content produced by traditional media, while Šķestere and Darģis (2022) showed that the agenda-setting process has been transformed by the dramatic growth of audiences that are simultaneously media consumers and producers. All these studies examined news content related to the main issues of the pandemic crisis, such as patients, vaccines, treatments and governmental policies.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, in terms of media type, existing research has focused on the role played by mainstream media yet neglected the power of We Media. Some studies have shown that official media failed to lead the discussion, whereas commercial media tended to be more influential than in the past in crisis cases ( Wang and Shi, 2022 ). Whether this conclusion is also able to be proven in the pandemic is still a question.…”
Section: Introductionmentioning
confidence: 99%